TEACHING OF HISTORY IN COLOMBIA: A VIEW FROM THE RESEARCH DISSEMINATED IN ARTICLES OF ACADEMIC JOURNALS - Hejeile Gutiérrez, Laura Viviana (2022)
The purpose for this article, is to provide look at the research and reflections about the teaching of history, disseminated through articles published in academic journals, in the last five years (2016-2021), with the aim of evidencing which are the topics of interest and the contributions that are proposed for the development of the field of history teaching in Colombia. From the analysis of the selected articles, it was possible to determine three approaches in which common perspectives converge: The interest in recent history; the concern for didactics and didactic resources for the history teaching; and the possibilities of regional history in school scenarios.